Penerapan model cooperative learning tipe teams games tournament (tgt) terhadap kemampuan penalaran matematika siswa pada pembelajaran matematika - Ade Sudarna; Abdul Rosyid; Ricki Yuliardi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
Students' mathematical reasoning in mathematics learning in Class VIII SMPN 1 Cibeureum of Kuningan Regency is still low. This is because the implementation of conventional learning model that less develop the ability to learn and build individuals. Conventional learning tends to minimize student involvement so teachers seem to be more active. The habit of being passive in the learning process can cause most students to be afraid and embarrassed to ask the teacher about the less interesting material. One of the learning model that is tried through this research is Teams Games Tournament (TGT) learning model. The problems in this research are: "Application of Cooperative Learning Type Teams Games Tournament Model (TGT) is better used in students' mathematical reasoning ability in mathematics learning compared with conventional model". The purpose of this research is to know the application of Teams Games Tournament (TGT) learning model to students' mathematical reasoning ability in learning mathematics. In this research the method used is experimental method. Surachmad (2001: 148) argued that "experimental method is a way to know the factors that cause the cause of the emergence of a result is to compare the events where there is a certain phenomenon. The population of this study are students of class VIII SMPN 1 Cibeureum Kuningan District. Sampling in this research using purposive sampling technique with M-G pattern that is using balancing technique average pretest value of control group and experiment group. There are 2 (two) variables in this study, namely: (1) Teams Games Tournament Learning Model (TGT) with conventional learning model, and (2) students' math competency. Data collection techniques used are documentation, tests, and questionnaires. Instrument test results (validity test, level of difficulty, distinguishing power) consisting of 5 items and used for pretest and postes are 5 items. Based on the results of validity, reliability, difficulty, and distinguishing test for pretest, postes, and questionnaires, all instruments are valid, reliable and can be used for data collection. The result of difference test of two pretest mean concluded there is no difference between experimental group and control group. The difference test of experimental group postes and control group was found that the experimental group was better than the control group. Average estimation in control group with mean of student learning result 54.21 while estimation of experiment group average with mean of learning result 56.53 mean experimental group result of student's mathematical ability ability on learning mathematics higher than with control group, hence there is influence Teams Games Tournament (TGT) learning model on students' mathematical reasoning ability in learning mathematics in grade VIII SMPN 1 Cibeureum of Kuningan. Based on the result of the research, it is concluded that learning using Teams Games Tournament (TGT) model is socialized and used as an alternative in learning mathematics in school. In addition to further research as the development of other research